Exploratory Analysis of Virtualization Tools in Delay-Sensitive Environment - Miroslav Voznak; Jiri Slachta; Filip Rezac; Jan Rozhon (Communications, 2013)
This article deals with an exploratory analysis of virtualized real-time applications. We compare selected virtualizations tools and present the achieved results in boxplots based on the performed exploratory analysis. The paper analyzes the impact of memory size and the number of processor cores on the delay itself and its variance in selected set of virtualization tools.